Assessing the Structure and Factors Affecting Agrobiodiversity of Home Garden at Katahari Rural Municipality, Province 1, Nepal - Khanal, S.; Khanal, D.; Kunwar, B. (Journal of Agriculture and Environment, 2019)
Available with full text.